RANCANG BANGUN APLIKASI REKAM MEDIS ELEKTRONIK DI KLINIK MEDIKA LESTARI JAKARTA PUSAT - Kusuma, Dodi Angga; Siregar, Kemal Nazaruddin; Prabawa, Artha; Yuniar, Popy; Diana; Yuliana, Enny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The implementation of Electronic Medical Records (RME) in all health service facilities is a digital transformation target in Indonesia. Clinics are health service facilities as the spearhead of primary level health services. However, there are still many clinics whose operations are still paper-based. The purpose of this study is to design an RME Clinical information system that produces precise and accurate data and information and uses RME variable guidelines and metadata to be ready to be integrated into the SATUSEHAT platform. The research design used in this research is qualitative. The system development method uses the System Development Life Cycle (SDLC) with the prototype method. The results of data collection found several problems in the implementation of medical records including paper-based, not standardized and structured diagnoses, medical record card storage was not efficient, report preparation was less effective. Based on this, a web-based clinical RME prototype was built. The resulting prototype makes clinical administration more efficient without a lot of paper/cards, standardized diagnostics, structured and safer data storage, and more effective report preparation because it is done through the system. Reports generated by the prototype can be used as a basis for clinical policies such as providing drug stock based on patient disease reports, as well as routine reports that are reported to the Puskesmas. This Clinical RME prototype can also be the forerunner of a clinical information system that wants to integrate RME with the SATUSEHAT platform.